Gli strumenti di pianificazione territoriale in relazione alla funzionalità dell’agricoltura periurbana - Giulia Giacchè; Chiara Mazzocchi (Projets de Paysage)
The paper focuses on the integration of periurban agriculture issues into territorial planning, as such integration appears to be largely insufficient at present considering the importance role recognized to periurban areas. The paper analyses the urban-planning instruments of two Italian regions (Lombardy and Lazio), characterized by wide agricultural areas and important metropolitan areas, as Milan in Lombardy and Rome in Lazio, highlighting the “image” of periurban agriculture, which emerges from these plans. The aim is to propose a reflection on the integration of agricultural functionality in the planning tools. In some contexts, as the periurban ones, the protection of green spaces is carried on by the permanence of farming, the only economic activity that could take care of the landscape; instead, often this function is not recognized by the urban policy. Hence the need to recognized a central role to agriculture in the land management recovering the functional role relating to the productive, social, environment conservation and protection and development of the agrarian landscape spheres.